Approximations of Multigrid Methods for Parabolic Quasi Variational Inequalities - Bahi, Mostefa (University Of Eloued جامعة الوادي, 2025)
In this thesis, we studied the multigrid method for parabolic quasi variational inqualities. For geting the discrete problem , we used the finite element method on the space and the difference method on the time, where, the discrete problem is equivalent the continuous problem . After that, we proved the uniform convergence of the multigrid method , for soloving the solution of our problem ,we trasfometed the parabolic quasi variational inqualities to the HJB equation , because there is an equivalence between the parabolic quasi variational inqualities and the HJB equation. In the applied branch, we gived a numerical applications for each studied problems, through which we confirmed the validity of the results obtained in the theoretical part. الملخص في هذه الأطروحة ، درسنا التقارب المنتظم لطريقة متعدد الشبكات ، والتي استعملناها في حل عدة أصناف خطية وغير خطية ، من المتراحات شبه التغيراتية ، حيث قمنا بصياغة كل متراجحة على شكل معادلة جاكوبي بلمان هميلتون الشهيرة ، وأثبتنا كذلك أن هناك تكافؤ بينهما ، في المسألة المتقطعة ، استخدما طريقة العناصر المنتهية للمؤثر وطريقة الفروق المنتهية للزمن ، ثم برهنا التقارب المنتزم لطريقة متعدد الشبكات ،ثم تد تدعيم النتائج النظرية بتطبيقات عددية
Thesis
Keywords: Parabolic variational inqualities; Finite element scheme; HJB-equation; multigrid techinc; المتراجحة التغيراتية المكافئة; ، طريقة العناصر المنتهية; طريقة الفروق المنتهية; طريقة متعدد الشبكات; HJB معادلة